KONTRIBUSI KOMPOSISI VEGETASI DALAM PENYIMPANAN DAN SERAPAN KARBON DI HUTAN RAKYAT DESA NEGARA RATU II KECAMATAN NATAR KABUPATEN LAMPUNG SELATAN - Dian Afriansyah; Duryat Duryat; Hari Kaskoyo (Jurnal Belantara, 2019)
Tree stands in community forest have potential to absorb carbon in the air by storing in the body parts of the tree.  This study aims to determine the effect of community forest’s stand types on the number of reserves and carbon uptake.  The sampling method used is the cluster sampling method to determine the sample.  Biomass data are collection destructive and non destructive methods.  Estimation of biomass is carried out using the allometric equations.  Measurement of carbon content using the formula from BSN (2011) x 0.47.  Comparative  analysis of carbon reserves and removals uptake using the variance test  and 5 % BNT test.  Public  forests in the Negara Ratu II village with gold teak stands have carbon reserves and removals (135.87 tons/ha and 499,00 ton/ha). the most significant compared to community forests with other types of stands. While the reserve value and carbon uptake between white teak (44.86 tons/ha and 164.63 tons/ha), acacia (54.13 tons/ha and 191.20 tons/ ha), red jabon (51.20ton/ha and 187.90 tons/ha), white jabon (59.51 tons/ha and 218.40 tons/ha), is no different.